2023
DOI: 10.1152/jn.00173.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor integration and motor learning during a novel visuomotor tracing task in young adults with attention-deficit/hyperactivity disorder

Abstract: Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that has noted alterations to motor performance and coordination, potentially affecting learning processes and the acquisition of motor skills. This work will provide insight into the role of altered neural processing and sensorimotor integration (SMI) while learning a novel visuomotor task in young adults with ADHD. This work compared adults with ADHD (n = 12) to neurotypical controls (n = 16), utilizing a novel visuomotor tracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…If this is the case, it may be a result of altered neural structure and function in those with ADHD, such as those in prefrontal cortical regions ( Barkley, 1997 ; Sowell et al, 2003 ; Seidman et al, 2006 ), affecting processes related to SMI. McCracken et al (2022) also showed a reduction in the N30 in those with ADHD compared to a control group whose N30 SEP peak increased post motor-acquisition. In the future, incorporating further assessment techniques that are sensitive to neural activity, such as fMRI or source localization, as an initial cost-effective starting point, would elucidate the role of localized neural regions or structures in such processes, which may prove to be invaluable, to further enhance the understanding of how ADHD influences motor learning and SMI.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…If this is the case, it may be a result of altered neural structure and function in those with ADHD, such as those in prefrontal cortical regions ( Barkley, 1997 ; Sowell et al, 2003 ; Seidman et al, 2006 ), affecting processes related to SMI. McCracken et al (2022) also showed a reduction in the N30 in those with ADHD compared to a control group whose N30 SEP peak increased post motor-acquisition. In the future, incorporating further assessment techniques that are sensitive to neural activity, such as fMRI or source localization, as an initial cost-effective starting point, would elucidate the role of localized neural regions or structures in such processes, which may prove to be invaluable, to further enhance the understanding of how ADHD influences motor learning and SMI.…”
Section: Discussionmentioning
confidence: 77%
“…The results from the current study suggest that those in the ADHD group may experience difficulty with the proprioceptive-centric demands of the current task, resulting in an enhanced dependence on force-modulation afferents via error monitoring, reflecting reduced inhibitory activity at the level of the cerebellum as a reduction in the N18 post motor acquisition ( Andrew et al, 2018 ). Interestingly, McCracken et al (2022) found contrasting results in those with ADHD when performing a motor acquisition paradigm utilizing different task demands. When completing a visuomotor task, those with ADHD had an increase in the N18, whereas controls had a decrease ( McCracken et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants could not have recurrent or chronic neck pain, indicated by a score of less than 5 on the Neck Disability Index [48]. Participants who had any of the following conditions were excluded as they may alter electroencephalography (EEG) suitability and/or impact central processing, such as: multiple sclerosis, epilepsy, seizure disorders, recurrent neck pain, autism spectrum disorder (ASD), and attention deficit hyperactivity disorder (ADHD) [13,23,28,35,[49][50][51]. This research was reviewed by the University of Ontario Institute of Technology (Ontario Tech University) Research Ethics Board and received ethical approval [REB #16520].…”
Section: Participantsmentioning
confidence: 99%
“…This has been seen as impaired upper limb performance accuracy [15,16], proprioception [17][18][19][20][21][22], and sensorimotor adaptation with respect to motor acquisition both neuronally and behaviorally [13,23,24]. Neuronal changes in response to motor skill acquisition have been quantified using somatosensory evoked potentials (SEPs), demonstrating changes in early (short-latency) SEP peaks related to SMI [14,[25][26][27][28]. Somatosensory evoked potentials (SEPs) are complex waveforms that are generated in response to the external somatosensory stimulation of the peripheral nerve of interest [10] as they pass along neural generators via the dorsal column medial lemniscus pathway.…”
Section: Introductionmentioning
confidence: 99%